2020
DOI: 10.3390/f11121281
|View full text |Cite
|
Sign up to set email alerts
|

The Cryobiotechnology of Oaks: An Integration of Approaches for the Long-Term Ex Situ Conservation of Quercus Species

Abstract: Conventional dry seed storage is unlikely for about one third of all tree species (and nearly half of evergreen rain forest trees) as they probably produce desiccation sensitive (recalcitrant) seeds. Consequently, international ex situ conservation targets for threatened trees will be difficult to achieve without innovation, especially in cryobiotechnology. We assessed progress in the development of various cryobiotechnology approaches for the preservation of oaks (Quercus), which are keystone species of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 84 publications
0
21
0
Order By: Relevance
“…These discrepancies, in both the lack of a universal method for plant cryopreservation and in the levels of initial percentage of plant regeneration between cryopreserved plant collections and conventional seed banking, have often been a barrier for the establishment of cryopreserved collections of wild species within seed banks. However, this has not been the case for crop plants [12,82] and we think similar standards of success should be applied to wild and threatened 'exceptional species' [83]. In this regard, cryopreserved plant accessions of wild species can be viewed like the elements of metacollections described in a previous section of this paper.…”
Section: Cryopreserved Plant Collectionsmentioning
confidence: 95%
See 1 more Smart Citation
“…These discrepancies, in both the lack of a universal method for plant cryopreservation and in the levels of initial percentage of plant regeneration between cryopreserved plant collections and conventional seed banking, have often been a barrier for the establishment of cryopreserved collections of wild species within seed banks. However, this has not been the case for crop plants [12,82] and we think similar standards of success should be applied to wild and threatened 'exceptional species' [83]. In this regard, cryopreserved plant accessions of wild species can be viewed like the elements of metacollections described in a previous section of this paper.…”
Section: Cryopreserved Plant Collectionsmentioning
confidence: 95%
“…Secondly, conventional seed banks and botanic gardens need to invest in infrastructure and specialised training to increase the taxonomic and geographic variation of cryopreserved collections of wild plant species (the scale of the investment will depend on the scale of the cryobank desired). Thirdly, cryobiotechnological research needs to be increased if more species and tissues are to be successfully cryopreserved [12,[83][84][85][89][90][91]. Fourthly, we must strengthen networking between wild species genebanks and crop genebanks to facilitate the preservation of wild species collections at the regional level in their crop genebank cryobank facilities, particularly in tropical areas where funding, a stable supply of liquid nitrogen and training for the development of wild species cryopreserved collections may be challenging [84].…”
Section: Cryopreserved Plant Collectionsmentioning
confidence: 99%
“…The importance of using appropriate, matching, diverse, and improved germplasm in forestry systems and the need for appropriate seed and seedling production systems are now being appreciated more. Ex-situ conservation ensures the survival of genetic resources [27][28][29][30]; in the case of forest genetic resources, this involves the storage of seeds, ensuring that they remain in suitable, species-specific conditions [31][32][33][34][35][36][37][38][39][40][41]. Skillful, effective seed storage provides a stable source of genetic diversity of forest trees needed for forest conservation.…”
Section: Forest Trees-ecosystems Important To Humansmentioning
confidence: 99%
“…Axillary budding enables conservation of selected genotypes but is expensive and has the additional risk of contamination and somaclonal variation [29]. To prevent these risks, the period between each subculture event could be increased (thus reducing costs) by applying slow growth methods [30,31] or by completely inhibiting growth (cryobiotechnology) [29,32]. To date, very few studies have investigated preservation procedures in holm oak, such as cold storage to preserve established axillary shoots from juvenile plants [30], while in [33], the authors reported the cryopreservation of holm oak somatic embryos in a procedure that did not enable long-term preservation.…”
Section: Introductionmentioning
confidence: 99%